PENGEMBANGAN APLIKASI KEUANGAN DAN PEMASARAN DARING UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT KOTA SURABAYA [THE DEVELOPMENT OF ONLINE FINANCIAL AND MARKETING APPLICATION TO IMPROVE THE COMMUNITY ECONOMY IN SURABAYA] - Surya Priyambudi; Yulis Setyowati; Alfi Nugroho (Universitas Pelita Harapan, 2020)
In the era of industry 4.0 technology development various modern food has grew abundantly that boomed and became viral in the community, this is just because that people’s mind set changed on food, their taste became simpler and instantly food. One of the food that become popular nowadays is fruit salad. Fruit salad is some fruits which have cut into pieces flavored with variant mayonnaise. This kind of fruit salad is became one of the most favorite food because it’s tasty. Observation and interview have been conducted in Sumberan, Pakal, Surabaya as the partner of this community service. As stated in observation and interview, the problems of the partner are: 1) Lack of concern on hygienic factors in processing fruit salad; 2) The process of packing fruit salad is not well done properly; 3) Human resources management are not managed well in the distribution of work; 4) Finance Bookkeeping had not conducted at regular intervals; and 5) Marketing and promotion has not yet to empower information technology.Due that problems, the team offered the solution as follows: 1) Supplying hygienic equipment in making fruit salad; 2) supplying an appropriate equipment packaging; 3) Training and workshop to improve packaging design to improve wrapping; 4) Refinement the label design in accordance to ‘PIRT’ regulation; 5) Training and workshop on human resources management, especially in the work distribution; 6) Training and workshop in finance bookkeeping which use online financial application; 7) Training and workshop on online marketing media for instance Ecommerce, WhatsApp business, Facebook, Instagram etc. The aims of this activity to increase the community economy and to produce hygienic, fresh and tasteful fruit in order to be consumed healthy.BAHASA INDONESIA ABSTRACT: Dalam era perkembangan teknologi industry 4.0, banyak berkembang olahan makanan modern yang merebak di masyarakat, hal ini diakibatkan oleh perubahan pola pikir masyarakat yang menginginkan varian makanan instan, salah satu yang mulai berkembang saat ini adalah salad buah. Salad buah merupakan salahsatu jenis makanan yang merupakan campuran dari potongan buah-buahan diberi varian mayonaise yang disukai banyak kalangan karena lezat dan segar. Berdasarkan observasi dan wawancara yang dilakukan kepada mitra beralamatkan Pakal Sumberan, Kecamatan Pakal, Kota Surabaya. Permasalahan pada mitra adalah; 1)Dalam pengolahan salad buah kurang memperdulikan faktor higienitas, 2)Proses pengemasan salad buah belum sempurna, 3)Manajemen SDM tidak dikelola dengan baik dalam pembagian kerja, 4)Pembukuan keuangan tidak dilakukan secara berkala, dan 5)Belum memaksimalkan pemasaran dengan media teknologi informasi. Solusi yang dipergunakan pada mitra adalah; 1)Pengadaan perlengkapan yang higienis dalam pembuatan salad buah, 2)Pengadaan alat pengemasan yang lebih baik, 3) Pelatihan pengemasan agar tampilannya lebih menarik, 4)Perbaikan desain label kemasan dengan menyesuaikan aturan PIRT, 5)Pelatihan pada manajemen SDM terutama dalam pembagian kerja, 6)Pelatihan pembukuan keuangan menggunakan aplikasi keuangan daring, 7)Pelatihan pemasaran menggunakan media daring, seperti: eCommerce, WhatsApp Business, Facebook, Instagram dll. Tujuan dalam kegiatan ini untuk memperbaiki perekonomian masyarakat dan menghasilkan olahan buah segar yang higienis agar sehat untuk dikonsumsi.